Analysis of water quality using physico-chemical parameters in Charcha colliery, Korea district, Chhattisgarh, India - Dwivedi, Pratima Rani; Augur, M R; Agrawal, Anita (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> This study was aimed to estimate current status of physico-chemical characteristic of Charcha colliery, at Korea District, Chhattisgarh. Monthly variation in physico- chemical parameters such as water temperature, pH, turbidity, total dissolved solids, total hardness, chlorides, phosphate, nitrates, dissolved oxygen and biological oxygen demand were analyzed for a April-may month 2012. The results indicated that physico-chemical parameters of the water were within the permissible limits and can be used for domestic, irrigation and pisciculture. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>